Inovasi media pembelajaran dengan alat bantu untuk meningkatkan kemampuan motorik siswa berkebutuhan khusus dan tunanetra - Kardiyanto, Deddy Whinata; Angga, Prayogi Dwina; Setiyawan, Andri Asrul (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This study addresses the limited variations in tactile movement learning, mobility, and jumping exercises that support the cognitive, psychomotor, and affective abilities of blind students with special needs. The purpose of this research is to enhance students' movement, mobility, and jumping skills through the use of embossed mat media in a frog-jumping exercise. A development method was employed, involving a small-scale trial with 3 students and a large-scale trial with 11 students. The study utilises descriptive percentage analysis and qualitative analysis methods to examine recommendations and rationales for response selection. Data from the small-scale trials show the following results: adaptive PE expert 1 at 89.33%, adaptive PE expert 2 at 93.33%, and learning expert at 80.00%. On a larger scale, adaptive PE expert 1 rated 93.33%, adaptive PE expert 2 rated 89.33%, and the learning expert rated 82.66%, yielding an average score of 88.44%. The percentage results for the embossed mat indicate that the product meets the "good" criteria based on the data analysis. The study concludes that the embossed mat media can be effectively used to teach frog jumping to blind students with special needs. It is recommended that teachers adopt this media and consider incorporating additional variations in PE learning for students with special needs.